(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to assess the experiences of patients and their family members during otorhinolaryngology consultations at the General and Occupational Health Outpatient Clinic. Subjects and methods: A cross-sectional descriptive study was conducted on 242 patients and accompanying family members aged 18 years and older who received otorhinolaryngology services at the clinic in 2024. The survey instrument was adapted from the SOPEQ tool developed by Eliza Lai-Yi Wong et al (2014), with modifications and additions to suit the specific context of the clinic. The questionnaire comprised 10 dimensions and 44 items, with a Cronbach’s alpha reliability coefficient of 0.962. Results: Among the participants, 55.4% were male, and 77.4% lived within 5 kilometers of the clinic. The overall positive experience rate was 94.2%. The highest-rated experience dimension was the consultation process (96.5%), while the lowest was the experience upon leaving the clinic (90.9%). The proportion of participants who were willing to return or recommend the service to their relatives was 95%. Conclusion: There is a need to further enhance patient and family experiences at the clinic. The study also recommends conducting future qualitative studies and regular surveys to continuously evaluate and improve service quality.